PEMANFAATAN KOMODITAS PANGAN LOKAL SEBAGAI SUMBER PANGAN ALTERNATIF DI PAPUA - A. Wahid Rauf; Martina Sri Lestari (Badan Penelitian dan Pengembangan Pertanian, 2009)
Utilization of local food as alternative food sources in PapuaPapua Province has a potential biodiversity including local food sources. Local food in Papua that has been used as main sources of carbohydrate for the local people are sago, millet, and root crops (sweet potato, taro, and yam). Root crops are mostly cultivated and consumed by local people in the lowland to highland area, while the people staying at beach area generally consume sago as a primary food. Some kinds of sweet potato, taro, and sago were adapted and consumed by local people for generation. In this case, those commodities must be developing as primary food sources for local community and also as substitute for rice. Besides utilized as primary food and important materials for ceremonial customs by local people, local foods has also been initiated for developing product diversification by home industry. This article discussed utilization of local food of Papua as an alternative food source, with main emphasize on root crops and sago, to support regional and national food security.